Lower Division Education at Berkeley The Students' Assessment - Koon, Jeff, Comp.; California Univ., Berkeley ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
Results of a lower division program evaluation questionnaire administered to freshmen and sophomores at the University of California at Berkeley are presented. Major areas of the survey were: departmental course evaluations; advising; faculty and their teaching; curriculum, courses, and content; competition, testing, grading, and student workload and performance; student participation in university governance; and overall satisfaction and the contributions of the university. Characteristics of the student population and methods of analysis are described and recommendations are offered. A sample questionnaire is appended. (SW)
ERIC Note: Not available in hard copy due to marginal legibility of original.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Freshmen; College Students; Course Evaluation; Higher Education; Institutional Research; Questionnaires; State Colleges; Student Attitudes; Student Characteristics; Student College Relationship; Student Evaluation of Teacher Performance; Student Government; Student Participation; Student Teacher Relationship; University of California Berkeley; Reports, Research